Administração sistêmica de espermidina e arcaína altera a memória da tarefa de esquiva inibitória em ratos: envolvimento da dependência de estado - Ceretta, Ana Paula Chiapinotto (2006)
The polyamines, putrescine, spermidine and spermine, are present in high concentrations in the central nervous system and, because of their policationic nature, they can interact with diverse cellular anionic targets (nucleic acids and proteins) and modulate the learning and memory by interacting with the polyamine binding site at N-methyl-D-aspartate receptor. In this study we investigated the effects of the systemic administration of spermidine and arcaine on the memory of the inhibitory avoidance task in rats. It was also determined whether the effects of the spermidine and arcaine involve state dependence. The animals were trained in an inhibitory avoidance apparatus (0.4 mA, 3s) and tested in the same apparatus 24 hours later. Immediate post-training administration of spermidine (50 mg/kg, i.p.) improved, while arcaine (10 and 30 mg/kg, i.p.) impaired step-down latencies in the inhibitory avoidance test. Administration of spermidine (50 mg/kg, i.p.) 15 minutes before testing did not alter the performance of rats which were injected with spermidine (50 mg/kg, i.p.) or vehicle immediately after training. However, administration of arcaine (30 mg/kg, i.p.) 15 minutes before testing reverted the impairment of memory caused by the administration of arcaine (30 mg/kg, i.p.) immediately after training. Administration of arcaine (30 mg/kg, i.p.) or MK-801 (0.03 mg/kg, i.p.) before testing partially reverted the impairment of memory caused by the administration of arcaine (30 mg/kg, i.p.) or MK-801 (0.03 mg/kg, i.p.) immediately after training, characterizing a crossed state dependence. The results suggest that memory improvement caused by the administration of spermidine immediately after training is not due to state dependence. In contrast, the impairment of memory induced by arcaine is due to state dependence. The crossed state dependence between arcaine and MK-801 supports that state dependence induced by arcaine is related to NMDA receptor hypofunction.